Cyclospora Genotypic Variations and Associated Epidemiologic Characteristics, United States, 2018–2021 - John Shen; Vitaliano A. Cama; David Jacobson; Joel Barratt; Anne Straily (Emerging Infectious Diseases)
Seasonal cyclosporiasis outbreaks occur in the United States every year. To better understand the disease, the Centers for Disease Control and Prevention developed a novel genotyping system that successfully clusters nonclonal eukaryotes. We examined temporal-geographic distributions of Cyclospora cluster consensus genotypes (CCGs) and applied regression analyses to identify correlations between Cyclospora spp. parasites and clinical manifestations or epidemiologic risk factors, using data collected during 2018–2021. No CCG was uniquely associated with or consistently detected in a state during the study, suggesting that cyclosporiasis in the United States is likely caused by frequent parasite introductions. We identified positive associations between infection with C. ashfordi and C. cayetanensis and consumption of specific produce items: cilantro, mango, and onion for C. ashfordi and iceberg lettuce, carrot, and cauliflower for C. cayetanensis. Our findings can guide future research into public health interventions aimed at reducing the burden of cyclosporiasis in the United States.